2017
DOI: 10.1007/s00253-017-8336-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacterial community responses to revegetation of moving sand dune in semi-arid grassland

Abstract: Grasslands in semi-arid Northern China are widely desertified, thus inducing the formation of a large area of moving sand lands. Revegetation of the sandy land is commonly adopted to restore degraded grasslands. The structure of the soil microbial community might dramatically change during degradation and recovery because microorganisms are one of the major drivers of ecological process through their interactions with plants and soil. Assuming that soil properties are the key determinants of the structure of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
3
20
2
Order By: Relevance
“…However, prokaryotic α-diversity increased from the unfixed sands to the mature soil on Site I, while prokaryotic communities of all samples on Site II did not follow the same pattern, and their α-diversities did not change with the successional stage. The obtained results partly contradict previously discovered trends of incremental growth of prokaryotic α-diversity during revegetation on moving dunes [10]. However, some studies reported the highest prokaryotic diversity at the early stages of soil formation [59,60].…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…However, prokaryotic α-diversity increased from the unfixed sands to the mature soil on Site I, while prokaryotic communities of all samples on Site II did not follow the same pattern, and their α-diversities did not change with the successional stage. The obtained results partly contradict previously discovered trends of incremental growth of prokaryotic α-diversity during revegetation on moving dunes [10]. However, some studies reported the highest prokaryotic diversity at the early stages of soil formation [59,60].…”
Section: Discussioncontrasting
confidence: 68%
“…Currently, chronosequences of soil formation can be observed in areas with variable climatic conditions and on omnigenous parent material, such as glacial retreats [14], sand dunes [57], volcanic rocks [8], or anthropogenic landscapes [9]. Changes in microbial community structure during the process of sand dune fixation have mostly been studied for arid and semi-arid regions [6,10,11] and for coastal environments [5]. Currently, successional traits during sand fixation in the cold climate of the tundra have received increasing attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prokaryotic α-diversity increased from the unfixed sands to the mature soil on Site I, while prokaryotic communities of all samples on Site II did not follow the same pattern, and their α-diversities did not change with the successional stage. The obtained results somewhat contradict previously discovered trends of incremental growth of prokaryotic α-diversity during revegetation on moving dunes [10]. However, some studies reported the highest prokaryotic diversity at the early stages of soil formation [57,58].…”
Section: Discussioncontrasting
confidence: 79%
“…In degraded sandy grasslands in semi-arid regions (even degraded to moving dunes), the community structure of soil bacteria can be reversibly restored by planting shrubs or semi-shrubs (including C . microphylla ) [29]. However, in-depth investigations of rhizosphere bacterial communities of C .…”
Section: Introductionmentioning
confidence: 99%